Nurses’ Knowledge regarding Infection Prevention in Neutropenic Patients at Tertiary Cancer Hospital, Nepal - Koirala, Sushila; Upreti, Shila; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2024)
Background:Neutropenia is one most common risk factor for infection and the leading causes of death in cancer patients that may results in unexpected hospitalizations and disruption in treatment plans and regimens. Method: A cross-sectional study was carried out among 100 nurses to assess the knowledge regarding infection prevention in neutropenic patients to those who are working least 6 months in chemotherapy of B.P. Koirala Memorial Cancer Hospital (BPKMCH). A non-probability purposive sampling technique was adopted to select the sample and the data was collected through a structured self- administered questionnaire. Data were analyzed by using Statistical Package for Social Science (SPSS) version 22. Result: The study findings summarized the level of knowledge into three categories where more than half (51%) of the respondents had good level of knowledge, 46% had moderate knowledge and 3% had poor knowledge regarding infection prevention in neutropenic patients. Conclusion: Though majority of the respondents had good and moderate level of knowledge regarding infection prevention in neutropenic patients but there is still lack of Guideline/Protocol on infection prevention measures and gap in knowledge regarding daily nursing assessment. So, there is still need to develop and implement infection prevention guidelines/ protocols and regular trainings on infection prevention from concern authority of hospital management.